Ecological determinants of fungal diversity on deadwood in European forests - Kuffer, Nicolas; Gillet, François; Senn-Irlet, Béatrice; Aragno, Michel; Job, Daniel (My University, 2008)
The fine-scale ecological determinants for wood-inhabiting aphyllophoroid basidiomycetes were investigated with statistical analyses of the occurrence of fruit bodies on woody debris collected in Switzerland and Ukraine. Three substrate descriptors were considered: diameter, degree of decomposition to those local environmental descriptors were detected. Three classes for diameter, as well as for degree of decomposition were thus delimited. They revealed the importance of very small sizes, which were not reported in the literature so far: the relevant diameter class limits were about 0.72 cm and 1.35 cm. Within the host tree species, a clear distinction between coniferous and broadleaf species was found. The next splits followed rather climatic determinants of tree distribution than taxonomical entities such as families or genera. The fidelity of the 59 fungal species to diameter classes, decomposition classes and host tree species was measured by the Dufrene-Legendre index and only significant responses after permutation tests were retained. This brought new insights on the ecology of many wood-inhabiting aphyllophoroid basidiomycetes. Redundancy Analysis was applied to investigate the response of fungal species to diameter and degree of decompostion of woody debris from the most common host tree species, Fagus sylvatica. This direct gradient analysis made it possible to reconstruct the succession of fungal species along the wood decomposition process.
Keywords: basidiomycetes; decomposition; diameter fungal ecology; host tree; species; woody debris; DECAYING BEECH LOGS; INSUBRIAN SOUTHERN ALPS; WOOD-INHABITING FUNGI; SPECIES RICHNESS; DEBRIS; COMMUNITIES; HISTORY; COARSE; NORWAY; MATTER